The Domain-Specific Constraint Approach to Prosodic Phonology: Evidence From Picard - Cardoso, Walcir (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2000)
This study presents a domain-specific constraint analysis for the processes of Semivocalization, Vowel Elision, Heterosyllabification and Across-Word Regressive Assimilation in Picard, a Gallo-Romance dialect spoken in the Picardie region in Northern France. In the study, I adopt the view hinted at in McCarthy and Prince (1995) and discussed in Pater (1996) that constraints can be decomposed into distinct domain-specific constraints, each with an independent hierarchical status within a single grammar. The advantage of such an approach is that it implies the existence of a single grammar. This is more advantageous from the point of view of language acquisition, since the language learner will have to master one single grammar. Moreover, the approach is more harmonious with other issues in the phonology of Picard, for which the decomposition of general constraints is necessary.